Transforming Africa’s Food System with Digital Technologies - Youssefi, Farbod (2019)
Farbod Youssefi POLICY SEMINAR Transforming Africa’s Food System with Digital Technologies Co-Organized by the Malabo Montpellier Panel and IFPRI NOV 26, 2019 - 09:30 AM TO 11:00 AM EST